Analysis and theoretical modeling of the 18O enriched carbon dioxide spectrum by CRDS near 1.35 μm: (I) 16O12C18O, 16O12C17O, 12C16O2 and 13C16O2. (January 2017) - Kassi, S.; Karlovets, E.V.; Tashkun, S.A.; Perevalov, V.I.; Campargue, A.
Abstract: The room temperature absorption spectrum of 18 O enriched carbon dioxide has been recorded by very high-sensitivity Cavity Ring Down spectroscopy between 6977 and 7918 cm −1 (1.43−1.26 μm). The achieved sensitivity (noise equivalent absorption α min ~8×10 −11  cm −1 ) has allowed for the detection of more than 8600 lines belonging to 166 bands of eleven carbon dioxide isotopologues. Line intensities of the weakest observed transitions are on the order of 2×10 −30  cm/molecule. In this first part, we present the results relative to the 16 O 12 C 18 O, 16 O 12 C 17 O, 12 C 16 O2 and 13 C 16 O2 isotopologues. Their absorption lines were rovibrationally assigned on the basis of the predictions of their respective effective Hamiltonian model. Overall 5476 lines were measured and assigned to 93 bands. Forty nine of them, all belonging to 16 O 12 C 18 O and 16 O 12 C 17 O, are reported for the first time. The studied spectral region is formed by Δ P =10–12 series of transitions, where P =2 V 1 + V 2 +3 V 3 is the polyad number ( V i are vibrational quantum numbers). The spectroscopic parameters of 58 bands of 16 O 12 C 18 O and 16 O 12 C 17 O were determined from a fit of the measured line positions. An inter- and an intrapolyad resonance perturbation were identified and analyzed in the 16 O 12 C 18 O spectrum. The comparison with the line positions and line intensities included in the AMES line list is discussed. Global fits of the line intensities were performed in order to (i) improve the Δ P =10 and 11 sets of the effective dipole moment parameters of 16 O 12 C 18 O and the Δ P =11 set of parameters of 16 O 12 C 17 O and (ii) derive for the first time the Δ P =10 and 12 parameters of 16 O 12 C 17 O and 16 O 12 C 18 O, respectively. Highlights: Cavity Ring Down spectroscopy of 18 O enriched CO2 between 6977 and 7918 cm −1 . 4243 transitions belonging to 59 bands of 16 O 12 C 18 O and 16 O 12 C 17 O are assigned. Thirty seven 16 O 12 C 18 O and twelve 16 O 12 C 17 O bands are newly assigned. Improved or new effective dipole moment parameters for Δ P =10–12 series of bands.